Does efavirenz replacement improve neurological function in treated HIV infection?. Issue 9 (1st March 2017) - Payne, B; Chadwick, TJ; Blamire, A; Anderson, KN; Parikh, J; Qian, J; Hynes, AM; Wilkinson, J; Price, DA; ,
Abstract : Objectives: The contribution of specific antiretroviral drugs to cognitive function in HIV‐infected people remains poorly understood. Efavirenz (EFV) may plausibly cause cognitive impairment. The objective of this study was therefore to determine whether chronic EFV therapy is a modifier of neurocognitive and neurometabolic function in the setting of suppressive highly active antiretroviral therapy. Methods: We performed an open‐label phase IV controlled trial. Adult subjects who were stable on suppressive EFV therapy for at least 6 months were switched to ritonavir‐boosted lopinavir (LPV/r) with no change in the nucleoside reverse transcriptase inhibitor (NRTI) backbone. The following parameters were assessed before and 10 weeks after therapy switch: cognitive function (by CogState ® computerized battery); brain metabolites (by proton magnetic resonance spectroscopy); brain activity [by attentional processing task‐based functional magnetic resonance imaging]; and sleep quantity and quality [by sleep diary, Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale]. Results: Sixteen subjects completed the study. Despite most subjects (81%) self‐reporting memory problems at baseline, cognitive function, brain metabolites, and brain activity showed no change at 10 weeks after switch. Sleep quality improved on switch off EFV [mean PSQI (standard deviation): EFV, 8.5 (6.5); LPV/r, 5.8 (5.5); mean difference −0.4; 95% confidence interval −6.0 to −0.7]. Conclusions: This is the first study to assess the effects of chronic EFV therapy on neurological function in a controlled setting. We conclude that EFV withdrawal is unlikely to result in significant modification of neurocognitive function in otherwise stable HIV‐infected people.